Conocimiento y uso ancestral de plantas medicinales en la comunidad nativa Awajún de Ajachim, distrito de Manseriche Loreto 2019 - Kuji Cruz, Michael (2021)
The main objective of this ethnographic study was to describe the knowledge and ancestral use of medicinal plants in the native Awajún community of Ájachim, made up of a total of 53 families (communal register), and had the support of key informants or knowledgeable people in this regard. wise men, indigenous mothers and families of the community. The methodological approach of this research was qualitative, ethnographic and descriptive in design, with data collection techniques: the semi-structured interview, participant observation and life stories. In addition, the data collection instruments were: the semi-structured interview guide and the observation guide, a camera, a tape recorder, a diary and a field notebook. In the data processing and analysis, semi-structured interviews were carried out, followed by transcription and selection of data following the steps of triangulation, conceptualization, categorization and structuring; Considering validity and reliability criteria, the Atlas.ti ° Program and ethnograf were also used. Conclusion: The Awajún de Ájachim native community makes traditional use of medicinal plants, which stands out for their cultural value, their transmission of ancestral knowledge and practices in the preparation, administration, care and diet to cure the most frequent diseases in the community and the following were identified: bellaco caspi (shipitna), sacha mangua (apai), ship agen, toé (ikante baikua), yahuar piri piri (kampanak), piri piri (punki pijipig), cotton (ujush), kaju agen, ajinger for colic (kaju agen), patiquina (sugkip), tsemantsem, ginger or kion (ajeg) and cat's claw (ajagke), each with its own characteristics that implies, preparation, care, dosage and diet of both the patient and the connoisseur, wise or indigenous mother, depending on the disease.